2016
DOI: 10.1186/s12883-016-0708-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pharmacological treatments for Lyme neuroborreliosis in children: a systematic review

Abstract: BackgroundMany aspects of pharmacological treatment of Lyme neuroborreliosis in children, such as choice of drug, dosage, and duration are subject to intense debates, leading to uncertainties in patients’ parents and healthcare providers alike. To assess the available evidence for pharmacological treatment for children with Lyme neuroborreliosis we conducted a systematic review.MethodsThe comprehensive systematic literature search included randomized-controlled trials (RCTs) and non-randomized studies (NRS) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
2
15
0
2
Order By: Relevance
“…* 3 for adolescents and adults weighing at least 50 kg. bid, twice daily; IU, international units; iv, intravenously; po, by mouth; qd, (once) daily; qid, four times daily; tid, three times daily antibiotics to treat Lyme neuroborreliosis in children; furthermore, the available studies are of poor quality (31). All of them do, however, appear to document a favorable prognosis of Lyme neuroborreliosis in children.…”
Section: The Treatment Of Lyme Neuroborreliosis In Childrenmentioning
confidence: 99%
“…* 3 for adolescents and adults weighing at least 50 kg. bid, twice daily; IU, international units; iv, intravenously; po, by mouth; qd, (once) daily; qid, four times daily; tid, three times daily antibiotics to treat Lyme neuroborreliosis in children; furthermore, the available studies are of poor quality (31). All of them do, however, appear to document a favorable prognosis of Lyme neuroborreliosis in children.…”
Section: The Treatment Of Lyme Neuroborreliosis In Childrenmentioning
confidence: 99%
“…In childhood, the first-choice oral antibiotic is amoxicillin (50 mg/kg/day up to a maximum dose of 500 mg/day), which is why in this case we decided to use it, although penicillin V sodium, and ceftriaxone may also be used 37 .…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of antibiotic therapy in children with Lyme borreliosis found no difference in therapeutic efficacy between different antibiotics 37 . Recurrences of Lyme borreliosis, especially third-stage arthritis, are treated with steroids 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Para ello, se emplean 2 a 3 semanas de penicilina-G, doxiciclina, cefuroxima, cefotaxima o ceftriaxona en la mayoría de los casos 26 . En la infancia, el antibiótico oral de primera elección es la amoxicilina (50 mg/kg/día hasta una dosis máxima de 500 mg/día), es por ello que en este caso decidimos emplear dicho antibiótico, aunque también se puede emplear penicilina-V sódica y ceftriaxona 37 . Una revisión sistemática de la antibiótico-terapia en niños con borreliosis de Lyme no encontró diferencias en la eficacia terapéutica entre los diferentes antibióticos 37 .…”
Section: Tiempo De Aparición Y Método Diagnósticounclassified
“…En la infancia, el antibiótico oral de primera elección es la amoxicilina (50 mg/kg/día hasta una dosis máxima de 500 mg/día), es por ello que en este caso decidimos emplear dicho antibiótico, aunque también se puede emplear penicilina-V sódica y ceftriaxona 37 . Una revisión sistemática de la antibiótico-terapia en niños con borreliosis de Lyme no encontró diferencias en la eficacia terapéutica entre los diferentes antibióticos 37 . Las recurrencias de la borreliosis de Lyme, sobre todo la artritis en tercera etapa se trata con esteroides 26 .…”
Section: Tiempo De Aparición Y Método Diagnósticounclassified